Incidence and Clinical Features of Immune-Related Acute Kidney Injury in Patients Receiving Programmed Cell Death Ligand-1 Inhibitors - Seethapathy, Harish (Kidney Int Rep, 2020)
BACKGROUND: Programmed cell death receptor ligand 1 (PD-L1) inhibitors are immune checkpoint inhibitors (ICIs) with a side effect profile that may differ from other classes of ICIs such as those directed against cytotoxic T-lymphocyte−associated protein 4 (CTLA-4) and programmed cell death 1 receptor (PD-1). Being the more recently approved class of checkpoint inhibitors, there are no studies investigating the frequency, etiology and predictors of acute kidney injury (AKI) in patients receiving PD-L1 inhibitors. METHODS: This was a retrospective cohort study of patients who received PD-L1 inhibitors during 2017 to 2018 in our healthcare system. AKI was defined by a ≥1.5-fold rise in serum creatinine from baseline. The etiology of all cases of sustained AKI (lasting >48 hours) and clinical course were determined by review of electronic health records. RESULTS: The final analysis included 599 patients. Within 12 months of ICI initiation, 104 patients (17%) experienced AKI, and 36 (6%) experienced sustained AKI; however, only 5 (<1%) experienced suspected PD-L1–related AKI. The PD-L1–related AKI occurred a median of 99 days after starting therapy. All patients concurrently received another medication known to cause acute interstitial nephritis (proton pump inhibitors, nonsteroidal anti-inflammatory drugs, or antibiotics) at the time of the suspected PDL1-related AKI. CONCLUSION: Although AKI is common in patients receiving PD-L1 therapy, the incidence of suspected PD-L1–related AKI is low (<1%) and may be less common when compared to other classes of ICIs. This cohort provides further validation that other drugs associated with acute interstitial nephritis may be involved in the pathogenesis of ICI-related AKI.